The Effects of Self-Regulated Learning and Peer Conformity on Students Academic Procrastination - Widodo, Sugeng; Wibowo, Mungin Eddy; Purwanto, Edy (Universitas Negeri Semarang, 2023)
Academic procrastination is an act of delaying the completion of academic tasks that lead to the decline in academic achievement. This study strived for analyzing the effects of self-regulated learning and peer conformity on academic procrastination. It used a correlational design and involved 72 students in grade eight at SMP Negeri 20 Semarang in the academic year of 2022/2023 as the sample. In analyzing the data, multiple linear regression test was used. Findings showed that self-regulated learning negatively correlated with academic procrastination, while peer conformity positively correlated with students’ academic procrastination. Thus, self-regulated learning and peer conformity need to become concern to give interventions for academic procrastination.